Coaching behind a mask. COVID-19 implications for the S&C Coach - Lim, J. (Science for Sport, 2020)
The ongoing pandemic has created some unique challenges for strength and conditioning (S&C) coaches to deliver their usual on-site training sessions. One of the hurdles that immediately stands out is the wearing of a face mask to coach indoors. Though cumbersome for a variety of reasons to be highlighted later in this article, it is highly recommended that all S&C coaches adhere to this health advisory.